When Schism Becomes Heresy in Late Antiquity: Developing Doctrinal Deviance in the Wounded Body of Christ - Tilley, Maureen A. (Journal of early Christian studies, 2007)
Over the last millennium, the terms "schism" and "heresy" have been defined and codified in theological manuals and canon law, yet their nature and differences were not always clear in antiquity. The possibility of heresy becoming schism or vice versa was conditioned not only by the declaration of ecclesiastical authorities but also by the fiat of civil authority. This essay explores early Christian attempts at differentiating the terms and uses organizational theory to analyze schism and heresy in North Africa and Rome in the third to fifth centuries.